Dosa Karena Lidah (Yakobus 3:1-12) - Delfiana Tena; Abad Jaya Zega (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Sin of the tongue is sin that comes out of the mouth and is expressed through words that are unpleasant for other people to hear. The tongue is a small part of the body, but it can also detect a person's physical condition through spoken words like those above. This means that someone can detect whether someone is mature in God or not, all of which can be known through the words they say. With the tongue, humans praise God's name, but with the same tongue, humans curse humans who were created in the image and likeness of Allah. From the same tongue come blessings and curses (Jas. 3:1-12). Here James emphasizes, "This, my brothers, must not happen to you" (Jas. 3:10). James reminds Christians who work as pastors or teachers to be careful in what they say because being a teacher is very difficult (Jas. 3:1). Christians need to control themselves in their pronunciation because they cannot be free from every mistake in the words that come out of their mouths, because they can have both positive and negative impacts. The purpose of writing is an effort to find answers to the main research points. The purpose of this writing is first, so that readers can understand the use of the tongue through correct words. Second, readers can gain a correct understanding of the sin of the tongue. Third, the reader gets a correct understanding of how to control the tongue. The research hypothesis is that it is suspected that there are people who do not properly understand the use of the tongue that God desires, so there are people who believe.